Pivotal Roles of GM-CSF in Autoimmunity and Inflammation - Aoi Shiomi; Takashi Usui (Hindawi Limited, 2015)
Granulocyte macrophage-colony stimulating factor (GM-CSF) is a hematopoietic growth factor, which stimulates the proliferation of granulocytes and macrophages from bone marrow precursor cells. In autoimmune and inflammatory diseases, Th17 cells have been considered as strong inducers of tissue inflammation. However, recent evidence indicates that GM-CSF has prominent proinflammatory functions and that this growth factor (not IL-17) is critical for the pathogenicity of CD4+ T cells. Therefore, the mechanism of GM-CSF-producing CD4+ T cell differentiation and the role of GM-CSF in the development of autoimmune and inflammatory diseases are gaining increasing attention. This review summarizes the latest knowledge of GM-CSF and its relationship with autoimmune and inflammatory diseases. The potential therapies targeting GM-CSF as well as their possible side effects have also been addressed in this review.